2015
DOI: 10.1007/s10934-015-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of superhydrophobic graphene/melamine composite sponge applied in treatment of oil pollution

Abstract: A facile chemical route to synthesize the graphene/melamine composite sponge with super oil adsorption capacity was reported. The effect of the graphene loading on the microstructures and adsorption property of the composite sponge was studied in detail. The adsorption capacity of diesel oil in composite sponge could reach 99.0 g/g. The oil adsorbed in composite sponge could be desorption in ethanol at 50°C. Furthermore, the composite sponge exhibited excellent mechanical and environmental stability. The facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 20 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…Absorption capacity is obviously higher than many recent reported sorbents (Table 1), such as nitrogen-rich carbon aerogel10, CNT/PDMS coated PU sponge27, highly hydrophobic, fire-resistant (UHF) sponge30, cellulose nanofibril aerogels45 and micro-wrinkled reduced GO46. The capacity of hBN coated sponge is also higher than that of melamine sponge coated with exfoliated graphene (165 g.g −1 , or 153 g.g −1 )1523, reduced graphene (99 g.g −1 )24 and MoS 2 (159 g.g −1 )26. And the value is comparable to the state-of-the-art new sorbents with high absorption capacity, for example, twisted carbon fibers (TCF) aerogel47, carbon microbelts aerogel48, thiourea reduced graphene sponge49, CVD-produced CNT sponge11, CNT-graphene hybrid aerogel50.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Absorption capacity is obviously higher than many recent reported sorbents (Table 1), such as nitrogen-rich carbon aerogel10, CNT/PDMS coated PU sponge27, highly hydrophobic, fire-resistant (UHF) sponge30, cellulose nanofibril aerogels45 and micro-wrinkled reduced GO46. The capacity of hBN coated sponge is also higher than that of melamine sponge coated with exfoliated graphene (165 g.g −1 , or 153 g.g −1 )1523, reduced graphene (99 g.g −1 )24 and MoS 2 (159 g.g −1 )26. And the value is comparable to the state-of-the-art new sorbents with high absorption capacity, for example, twisted carbon fibers (TCF) aerogel47, carbon microbelts aerogel48, thiourea reduced graphene sponge49, CVD-produced CNT sponge11, CNT-graphene hybrid aerogel50.…”
Section: Resultsmentioning
confidence: 99%
“…altered the size distribution of graphene sheets using a grinding method in isopropyl alcohol and SDS, the fabricated graphene-coated melamine sponge delivered an absorption capacity of 153 g.g −1 for chloroform15. Graphene oxide (GO) was also introduced to modified melamine sponges followed by hydrothermal or chemical reduction to remove the oxygen-containing groups of GO2425. The reduced GO-coated sponge exhibited adsorption capacity of 99 g.g −1 for diesel oil24.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [ 117 ] fabricated multifunctional mesh films containing GO–SiO 2 nanohybrids with underwater oleophobicity and antibacterial property which could be employed for effective oil water separation. Synthesis of graphene/melamine composite sponge with enhanced diesel absorption [99.0 g/g] was carried out by Liu et al [ 118 ] It was also found that the sponge had excellent mechanical and environmental stability. Similar works on graphene sponge was carried out by Zhao et al [ 119 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Based on the above considerations, the proper support remains an obstacle for the practical application of monolithic photocatalyst. Lately, melamine sponge (MS), a cheap commercial polymer foam which is widely used as kitchen and construction materials, is successfully used for oil-water separation by integrating with graphene (Liu T. T. et al, 2015 ; Zhao et al, 2016 ). The fabricated graphene/MS exhibits low-density, high porosity and high elasticity inherited from MS, which exactly match the support characteristics of the monolithic photocatalyst.…”
Section: Introductionmentioning
confidence: 99%